Awareness and acceptability of long-acting injectable pre-exposure prophylaxis for HIV prevention among female students at tertiary learning institutions: a multi-center, institution-based cross-sectional study - Martin Kampamba; Pumulo Munawai; Remmy Sioma; Christabel Mwila Hikaambo; Steward Mudenda; Mukumbi Mutenda; Jean M. Mukumbuta; Muchindu Hampango; Muzyamba Malambo; Gunet Mwalungali; Audrey Hamachila; Billy Chabalenge; et al. (BMC Public Health)
Abstract Background Adolescent girls and young women (AGYW) in Zambia face an elevated risk of acquiring HIV. Long-acting injectable pre-exposure prophylaxis (LAI-PrEP) is an effective scientific method to prevent new HIV infections. However, awareness and acceptability of LAI-PrEP among AGYW remain limited. Thus, we aimed to assess awareness and acceptability of LAI-PrEP among female students. Methods This multi-center, institution-based cross-sectional study involved 760 female students from three universities in Lusaka, Zambia. Data were collected using a structured, self-administered questionnaire. Questions on acceptability and awareness were presented in a yes/no format. Data analysis was performed using STATA version 15.1. Results Of the 760 participants, less than half, 349 (45.9%), were aware of injectable PrEP, with lectures being the most common source of information. In terms of acceptability, 531 (69.9%) of respondents indicated they would be willing to take LAI-PrEP once available. Biomedical science students were significantly less likely to accept injectable PrEP (AOR = 0.10, CI: 0.01–0.94, p = 0.044), as were those not at risk of HIV in the past three months (AOR = 0.41, CI: 0.21–0.81, p = 0.011). Conversely, knowing a partner’s HIV status (AOR = 2.52, CI: 1.27–4.98, p = 0.0001) and being at risk of HIV in the past three months (AOR = 3.4, CI: 1.78–7.81, p = 0.011) were significantly associated with LAI-PrEP acceptability. Conclusion The study revealed a notable gap in awareness of LAI-PrEP among participants, with less than half being informed about its existence. Despite this low awareness, a significant majority expressed a willingness to accept LAI-PrEP if it were made available to them. This indicates a strong potential for adoption of LAI-PrEP, contingent upon improved education and awareness efforts.